2016
DOI: 10.1111/maps.12675
|View full text |Cite
|
Sign up to set email alerts
|

The formation environment of potassic‐chloro‐hastingsite in the nakhlites MIL 03346 and pairs and NWA 5790: Insights from terrestrial chloro‐amphibole

Abstract: Potassic-chloro-hastingsite has been found in melt inclusions in MIL 03346, its paired stones, and NWA 5790. It is some of the most chlorine-rich amphibole ever analyzed. In this article, we evaluate what crystal chemistry, terrestrial analogs, and experiments have shown about how chlorine-dominant amphibole (chloro-amphibole) forms and apply these insights to the nakhlites. Chloro-amphibole is rare, with about a dozen identified localities on Earth. It is always rich in potassium and iron and poor in titanium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 123 publications
(210 reference statements)
3
29
0
Order By: Relevance
“…Fe°sponge (needed for combination with hematite to provide the desired ferrous/ferric ratio) and MgCl 2 (for the chlorine-bearing sources) were added in the last hour to mitigate any oxidation or dissolution of the components, respectively. The Fe 2+ / (Fe 2+ +Fe 3+ ) ratio of this mixture was determined by the MELTS (Ghiorso & Sack, 1995) analysis mentioned above. This analysis indicated that a log (fO 2 /1 bar) of -7 (~0.2 log units above NNO) at 1150°C would be achieved by setting the Fe 2+ /(Fe 2+ +Fe 3+ ) ratio of the synthetic source mixture to 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe°sponge (needed for combination with hematite to provide the desired ferrous/ferric ratio) and MgCl 2 (for the chlorine-bearing sources) were added in the last hour to mitigate any oxidation or dissolution of the components, respectively. The Fe 2+ / (Fe 2+ +Fe 3+ ) ratio of this mixture was determined by the MELTS (Ghiorso & Sack, 1995) analysis mentioned above. This analysis indicated that a log (fO 2 /1 bar) of -7 (~0.2 log units above NNO) at 1150°C would be achieved by setting the Fe 2+ /(Fe 2+ +Fe 3+ ) ratio of the synthetic source mixture to 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the ferrous/ferric ratio was set to be that of NNO at 1150°C in the starting source material. The value of this initial ratio was obtained by using the Irvine composition for a MELTS analysis (Ghiorso & Sack, 1995) of the effect of log (fO 2 /1 bar; that is, log fugacity of oxygen relative to a 1 bar standard state) on the melt Fe 3+ /Fe 2+ ratio.…”
Section: 1029/2018je005911mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of igneous rocks varying from basaltic to ultramafic compositions is inferred from the widespread occurrence of pyroxenes, olivine, and plagioclase, as observed by visible/near-infrared (VNIR), thermal infrared, and gamma ray spectrometers such as Observatoire pour la Minéralogie, l'Eau, les Glaces, et l'Activité, Compact Reconnaissance Imaging Spectrometer for Mars (CRISM), Thermal Emission Spectrometer, and Gamma Ray Spectrometer (e.g., Bibring et al, 2006;Boynton et al, 2007;Christensen et al, 2001;Murchie et al, 2007), in situ rock analyses on Mars (e.g., Brückner et al, 2003;Gellert et al, 2006;Ming et al, 2008;Schmidt et al, 2014;Squyres et al, 2012;Zipfel et al, 2011), and Martian meteorites of the shergottite, nakhlite, and chassignite group (Bridges & Warren, 2006;Meyer, 2013;Treiman, 2005;Treiman & Filiberto, 2015) and related basaltic meteorites (Agee et al, 2013). In addition, numerous alteration minerals have been identified, including clays, chlorite, mica, prehnite, epidote, zeolites, serpentine, carbonates, sulfates, hydrated (opaline) silica, oxides, scapolite, and Cl-rich amphibole (e.g., Arvidson et al, 2014;Carter et al, 2013;Changela & Bridges, 2010;Ehlmann et al, 2009;Filiberto et al, 2014;Gendrin et al, 2005;Giesting & Filiberto, 2016;Hicks et al, 2014;Milliken et al, 2008;Murchie et al, 2009;Poulet et al, 2005;Squyres et al, 2008;Treiman, 2005;Vaniman et al, 2014). The presence of hydrous phases indicates multiple diverse aqueous environments and episodes of activity.…”
Section: Introductionmentioning
confidence: 99%
“…Filiberto et al (2014) found evidence for high temperature fluids in the form of marialite (Na‐Cl scapolite) in a melt inclusion in Nakhla, which is consistent with formation from Cl‐rich, water‐poor fluid (either magma or brine) at a minimum temperature of 700 °C. Further evidence for Cl‐rich hydrothermal conditions has been found in other nakhlites in the form of Cl‐potassic‐hastingsite (e.g., Giesting and Filiberto 2016), which forms in medium‐grade metamorphic conditions (>400 °C). Finally, recent investigations of meteorite NW 7533 found eskolaite encased in chromite‐magnetite and suggested that it formed from an active hydrothermal environment in the Martian crust (Liu et al 2016).…”
Section: Introductionmentioning
confidence: 84%